Landflucht und Städtewachstum in der Türkei - Ritter, Gert (ERDKUNDE, 1972)
Since the 1950s the population of Turkey has been growing at the high rate of 2.5%. The difference between rural and urban development is due to a considerable rural-urban migration the proportion and direction of which can be inferred from the birthplace statistics. After a discussion of the outstanding push- and pull-factors of this migration and its demographic consequences the urban residences of the rural migrants are treated in detail. These so-called Gecekondus are mainly squatter colonies with high residential densities and a boxed up and introverted kind of structure, often lacking transport facilities as well as water and electricity supplies. As they are usually built up privately and without practical experience the Gecekondus tend to decline into slums especially when frequented by tenants. From their social and economic appearance the Gecekondu residences can be regarded as migratory stations between the traditional rural and the more progressive urban way of life thus fulfilling an important function within the process of industrial evolution in Turkey. Though they cannot in general be compared with slums or for instance the favellas in Latin America the Gecekondus are one of the outstanding problems in Turkey: in ten towns the proportion of people living in Gecekondus ranged from 30 to 60% already in 1960; town-planning is hampered and outrun by these problematic quarters and their rapid growth. The Gecekondu Act of 1966 has failed to stop this process mainly because the necessary social reforms and measures of regional development have been delayed by the Government.